Aerobic anoxygenic phototrophic bacteria and their photosynthetic membranes : imaging from macro- to nanoscale - Franz, Ole (2022)
While anaerobic anoxygenic phototrophic green or purple bacteria have been extensively researched, little is known about the ubiquity and function of aerobic anoxygenic phototrophic (AAP) bacteria in different environments. They perform photosynthesis in the presence of oxygen with the help of photosynthetic complexes including bacteriochlorophyll a. Equipped with this ability they have an advantage in oligotrophic environments. Previous research has focused on aquatic AAP bacteria, revealing new species, and developing hypotheses for their impact. Also, sometimes surprisingly high shares of procaryotic biomass comprised of AAP bacteria, for example in oligotrophic oceans, have been reported. However, functions and ubiquity of AAP bacteria in terrestrial environments have been neglected. Here, a self-built, low-cost imager for AAP bacteria detection is introduced. Based on UV-induced near-infrared fluorescence of bacteriochlorophyll a, it efficiently detected AAP bacteria colonies from environmental samples directly from Petri dishes. The method was compared with the commercially available option of using hyperspectral cameras for similar detection purposes. While the potential analysis depth of hyperspectral cameras proved to be larger, it was not possible to achieve a similarly specific and easy AAP bacteria identification with the here tested cameras and setups. Additionally, a method was developed to extract the photosynthetic membrane of Sphingomonas glacialis strain S2U11. Extracted material and whole cells were analyzed and compared spectroscopically, revealing that the extract contained intact photosynthetic complexes. Atomic force microscopy was used to image the isolated membranes and embedded protein complexes. The measured dimensions and packing of the photosynthetic structures fit well to the literature. However, the surrounding lipid bilayer measured only ~1 nm. The methods facilitate experiments with AAP bacteria previously reported only for anaerobic anoxygenic bacteria. They can help discovering differences between aerobic and anaerobic bacterial photosynthesis and species-specific novelties.